Safety and Effectiveness of Endoluminal Vacuum-Assisted Closure for Esophageal Defects: : Systematic Review and Meta-Analysis (Translation: The University of Toledo Journal of Medical Sciences, 2023)
Please view the PDF to see the formatted meeting abstract.
Keywords: Gastroenterology; Research